Entering new markets: nuclear industry challenges (Brazilian Journal of Radiation Sciences (BJRS), 2021)
Nuclear ship propulsion and isolated islands energy supply are unexplored markets for nuclear vendors. Carbon taxes and fuel regulations may make fossil fuels more expensive. Such markets pay more for energy because of organization and transport costs and use of small machines, which are less efficient than grid generators. The goal of this work is to find the measures the nuclear industry needs to take to get into new potential markets. This work shows the different actors and their interests and points the natural or physical constraints they face. Considering interests and constraints, this work named the most probable market niches where nuclear power may beat other power sources. After considering natural constraints, this paper analyses human-generated constraints and presents a way on how to mitigate or solve them. This study shows that nuclear industry needs to take technical, administrative, and political measures before nuclear power arrives to a wider market. This work is based on literature review and qualitative analysis and cannot point precise thresholds where nuclear power should be competitive. Future work will consist of statistical analysis to find precise thresholds to help in the decision-making process.